PENGARUH ORIENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KINERJA SOSIAL PERUSAHAAN DENGAN KETIDAKPASTIAN LINGKUNGAN SEBAGAI VARIABEL PEMODERASI - Puji Harto (Jurnal Akuntansi Indonesia, 2013)
The objective of this research is to investigates the relationship of company’s orientation toward social responsibility at small and medium enterprises to their social corporate performance. In addition, this research also examines the role of environmental uncertainty as the moderating variable in affecting the relationship of corporate social responsibility orientation and corporate social performance. Sample was taken from small and medium businesess in Jawa Tengah. Initial distribution of 300 set of questionnaires to SME respondents has resulted in final sample of 115 respondents that usable to the analysis stage. The results of this study show that company’s ethical orientation has positive relationship with corporate social performance, while company’s legal orientation has negative effect toward corporate social performance. Moreover, the presence of environmental uncertainty has resulted in two significant interactions with the two components of company’s orientation. The interaction of environmental uncertainty and company’s ethical orientation has negative relationship with corporate social performance. Similarly, the interaction of environmental uncertainty and company’s legal orientation has positive relationship with corporate social performance.